Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records - Yang, Liyuan; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2016)
The fauna of Thailand was previously known to include only a single species of Macropsini. Study of an extensive collection of recent Malaise trap samples from Thailand revealed the presence of five additional species of this leafhopper tribe, including two new species, Pediopsis thailandensis and Varicopsella odontoida spp. nov., described and illustrated herein; and three additional species, Macropsis hainanensis, P. rufoscutellata and V. elegans, previously recorded from neighboring countries. A key to genera and species of the Macropsini of Thailand is provided.